Cardiac responses and load during training and competition in wheelchair-basketball players - Olasagasti-Ibargoien, J.; Bidaurrazaga-Letona, I.; Gil, S. M. (European Journal of Human Movement, 2024)
The quantification and monitoring of training is vital to improve performance and to avoid fatigue and injuries. Heart rate and perceived exertion have been widely used to monitor load in able-bodied sports; however, concerning sports for people with disabilities, similar reasearch is limited. Moreover, the characteristics of the disability may influence the results. The aim of this study was to compare cardiac responses and load in wheelchair-basketball (WCB) players during training and matches, and to ascertain these indicators` relationship to players` functional classification. Heart rate (HR) and peripheral and central rating of perceived exertion (RPE) were recorded in a WCB team (n=15) during a season. Absolute and relative maximal and mean HR were calculated. Internal load was quantified using Edwards` summated-heart-rate-zones method. To enable comparisons, players were divided into low- and high-class groups according to the International Wheelchair Basketball Federation (IWBF) classification. Cardiac demand and load were higher in matches compared to training in both groups of players; however, RPE was only higher in high-class players. During training, low-class players displayed lower absolute maximal HR, but higher relative HR, than high-class players. The risk of underestimating the low absolute HR values of low-class players reinforces the value of relative HR values when monitoring load. On the other hand, for high-class players, coaches must ensure that they complete intense training, to generate the stimulus required for adaptations. For low-class players, RPE should be used with caution because it may not accurately reflect load and cardiac demand.